Amenizante orgânico e micorrizas arbusculares em mudas de eucalipto cultivadas em solo contaminado com cobre - Negrini, Alex (2017)
Anthropogenic activities have elevated copper levels in the soil making this chemical element toxic to plants. The use of plants associated or not with microorganisms, in addition to organic compounds with the purpose of minimizing the effects of the metals become interesting in this situation, to allow the revegetation of these soils contaminated with copper. To meet the objectives were conducted three experiments, In which the first one aimed to determine the growth, tolerance and accumulation of copper in Eucalyptus grandis, Eucalyptus saligna, Eucalyptus dunniii and Corymbia citriodora; The second one determined the mitigating effect of swine wastewater on soil contamination with copper and its influence on the growth of Eucalyptus grandis and Eucalyptus saligna; While the third, was determined the influence of the conjugated use of arbuscular mycorrhizal fungi and swine wastewater compost on the growth and accumulation of copper in Eucalyptus grandis. The results showed that the seedlings of Eucalyptus grandis, Eucalyptus saligna, Eucalyptus dunniii and Corymbia citriodora had their morphological parameters reduced with the doses of copper, most of the copper accumulated in the root, and greater tolerance of Eucalyptus grandis and Eucalyptus dunniii species. The swine wastewater compost provides higher growth, copper accumulation and seedling quality in the species of Eucalyptus grandis and Eucalyptus saligna. The addition of swine wastewater compost with the arbuscular mycorrhizal fungi inoculum Gigaspora margarita increases the morphological parameters, seedling quality and copper accumulation in Eucalyptus grandis seedlings grown in soil contaminated with copper.